A survey on graph partitioning approach to spectral clustering / SUBHANSHU GOYAL, SUSHIL KUMAR, ... [and others] - SUBHANSHU GOYAL
The clustering problem can be formulated as a graph cut problem where a suitable objective function has to be optimized. This study uses different graph cluster formulations based on graph cut and partitioning problems. A special class of graph clustering algorithm known as spectral clustering algorithms is used for the study. Two widely used spectral clustering algorithms are applied to explaining solution to these problems. These algorithms are generally based on the Eigen—decomposition of Laplacian matrices of either weighted or non-weighted graphs.